Optimalisasi Waktu Hambatan Excavator Untuk Mencapai Target Produksi Batubara Pit C CV Kutai Kumala Energy: Optimization Losstime of Excavator to Achieve Coal Production Target at Pit C CV Kutai Kumala Energy - Magdalena, Henny; Saksono, Fransiska Yuniari (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2024)
The barriers on the activity causes losstime. The losstime of excavator that so high cause coal production targets not to be achieved. Therefore efforts are made to improve the losstime. The analysis of multiple linear regression multivariate is used as a problem solving approach, namely finding the maximum limit of idle time and delay time and formulating the optimal losstime. Based on observations of the idle time and delay time of two excavator units operating in the morning shift, the regression equation is obtained Y = 1832.782 – 95.134X1. The equation of optimal losstime is X2 = -0.8729X1 + 10.71. The simulation is carried out based on the average actual data, the maximum idle time limit of 6.67 hours and a delay time of 4.89 hours. For an idle time of 4.45 hours, it is expected that the delay time will not exceed 6.83 hours in order to achieve the production target. The causes of unfulfilled of production were include rain, landslides, breakdown units, slippery, operator needs and et cetera.